Poverty in Bangladesh : Building on Progress - World Bank (Washington, DC, 2013)
Bangladesh has made recent progress in reducing poverty, but still faces the reality that roughly half its citizens live in deprivation. This report examines the record of advances during the 1990s, major challenges still to be overcome and priority measures to accelerate poverty reduction. The report suggests that changes in practices an policies, to realize healthy economic growth designed to benefit the rural poor as well as more rapid, sustained movement toward greater social justice. Dramatically lowering the incidence of poverty requires significantly higher levels of economic performance, it also requires that growth reaches the poor and expands their opportunities. Primary education managed to enroll nearly equal proportions of boys and girls and of urban and rural children. Drinking and cooking water now come from tube wells rather than from less sanitary surface water. Prioritizing use of governmental resources, correcting the deterioration that has taken place in government finances in recent years, and imposing strong discipline on the many wasteful state-owned enterprises would help restore fiscal order and macroeconomic stability.